Hubungan Kecanduan Game Online dengan Kualitas Tidur pada Mahasiswa Angkatan 2021 Fakultas Ekonomi Universitas Warmadewa - Made Aristia Utami; Sagung Putri Permana Lestari Murdhana Putere; I Gede Yudhi Kurniawan (Aesculapius Medical Journal, 2023)
[The Relationship between Online Game Addiction and Sleep Quality in Class of 2021 University Students, Faculty of Economics, Warmadewa University]Recently, technology is developing very rapidly. Of course these developments have an impact on development around the world. Technological developments, especially in the entertainment world, one of them we can feel through online games. Although game online can have a positive impact as entertainment, but on the other hand game online can have a negative impact on every individual who plays it, namely addiction. The phenomenon of game addiction game online can make someone play for a very long time, even to the point of ignoring other activities. Gamer spends 20-25 hours a week so the addiction to online games in university students can lead to problems meeting basic needs such sleeping and resting. A study said 47.17% of university students indicated an addiction to playing online games. This study aims to determine whether there is a relationship between online game addiction and sleep quality in the 2021 university students of the Faculty of Economics, Warmadewa University. This study used a cross sectional design. The use of sample selection was stratified random sampling technique. Collecting data on the incidence of online game addiction and sleep quality used a questionnaire. Data analysis was carried out univariate and bivariate. Bivariate analysis used Spearman rank correlation found a significant relationship between online game addiction and sleep quality (p = 0.000; r = 0.656). In this study, it can be concluded that there is a relationship between online game addiction and sleep quality in the 2021 university students of the Faculty of Economics, Warmadewa University. Keywords: Online games, game addiction, sleep quality, university student